PKM pendekatan pembelajaran kontekstual pada Guru- Guru Sekolah Dasar Negeri No. 80 Kota Parepare - Yonathan Saba; Pasinggi Pasinggi; Ritha Tuken (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Understanding contextual reading is an observation, initiative, tried, some of them to hear, follow, instructions.Contextual learning, teachers guide students weeks to find answers, make notes and conclusions from the book source, anddisplay the pictures show an example. From my observation the writer, colleague and self-reflection, then the identified problemlearning. Based on the problems experienced by primary teachers about teaching in class, then to overcome itpenyuluhmengambil inisyatif with classroom teachers to identify problems in the form of improved learning with a focus onefforts to